Paths of glory - Archer, Jeffrey, 1940- (Macmillan, 2009)
Some people have dreams that are so outrageous that if they were to achieve them, their place in history would be guaranteed. Francis Drake, Robert Scott, Percy Fawcett, Charles Lindbergh, Amy Johnson, Edmund Hillary and Neil Armstrong are among such individuals. But what if one man had such a dream, and when he'd fulfilled it, there was no proof that he had achieved his ambition?